Proposed Regulations for Enforcement of the Purports of Binding Banking Documents in Rastin Banking - Bidabad, Bijan; Abdollahi, Saeid; Sherafati, Mahshid; Mohammadi, Roohollah (International Journal of Small and Medium Enterprises, 2019)
To facilitate and accelerate the enforcement of binding banking documents and distribute the enforcement burden of the registration offices of the State Organization for Registration of Deeds and Properties, courts, and judicial authorities, a new mechanism for “enforcement of the purports of binding banking documents in Rastin Banking” was designed. This mechanism can lead to positive and essential effects toward creating public trust in financial obligations and increasing the speed of collecting demands, in order to remove the problems resulting from enforcement of the purports of binding documents. In this paper, the proposed regulations are presented in two drafts of “The Bill for Enforcement of the Purports of Binding Banking documents in Rastin Banking” and “The Bylaw for Enforcement of the Purports of Binding Banking Documents and Handling Complaints against Executive Operations in Rastin Banking”.The newly designed method has been compiled considering all financial, legal, and executive issues. In the proposed regulations, a part of the executive path for enforcement of the purports of binding banking documents is transferred from the “Document Registration Unit” into a newly established unit called the “Bank Documents Execution Unit” (BDEU), located in every bank, and this new unit will follow the enforcement of the purports of binding banking documents, instead of the “Document Registration Unit”. All the legal necessities, the necessary cooperation with the judicial authorities, and the necessary procedures for hearing and settlement have all been designed to not let any spoiling of the rights of the parties, while also working efficiently.This procedure is a model that can be adapted for other countries, especially those countries that have a large number of legal disputes and the process of dispute settlement is very lengthy and cumbersome. Since the Administration of Justice is the main factor to promote all the other social and economic circumstances, the proposed model can prepare a way to improve the social and economic well-being.